Virtual venues and international negotiations: Lessons from the COVID-19 pandemic - Bjola, C; Coplen, M (Brill, 2022)
The COVID-19 pandemic has altered international diplomacy, with many negotiations now conducted in ‘virtual venues’ facilitated by videoconferencing platforms such as Zoom, Microsoft Teams, Webex, and Interprefy. Drawing on a survey of diplomats with experience in virtual venue negotiation, we analyze respondents’ perceptions of efficacy, tactics, and legitimacy in these venues. We find that virtual venues not only affect the format, but also the substance of negotiations. In general, perceptions of efficacy are related to diplomats’ ability to ‘read the room’. Virtual venues also impact negotiations at the tactical level. We find that coercive approaches (including novel tactics) are more common than persuasive approaches. Overall, these venues are afforded the same legitimacy as face-to-face negotiations. We conclude that, as virtual venues will be a feature of international diplomacy for the foreseeable future, further research is required to inform increased diplomatic adaptation and hybridity.